The implementation of the flipped classroom approach to improve the EFL students’ reading ability - Septiani, Rahmah; Muluk, Safrul; Habiburrahim, Habiburrahim (Englisia: Journal of Language, Education, and Humanities, 2024)
Reading is a vital language skill that necessitates mastery for knowledge acquisition. However, the focus of students has shifted away from reading due to technological advancements. Despite this, the literacy levels of students in Indonesia are alarmingly low, ranking 74 out of 79 in the PISA Survey 2018. This study aimed to explore the integration of technology in educational settings. Specifically, by implementing a technology-based flipped classroom model, the researcher aimed to encourage and educate junior high school students on the constructive use of smartphones. The primary objective was to investigate whether the adoption of flipped classrooms, combined with technology utilization, could potentially enhance students' reading proficiency. To achieve this goal, an experimental research design was employed, comprising both an experimental group and a control group. Pre-tests and post-tests were conducted for both groups, with the experimental group receiving the flipped classroom intervention, while the control group experienced traditional classroom methods. The findings indicated that the experimental group exhibited superior performance compared to the control group.